LEGAL EFFORT OF THE GOVERNMENT AGAINST MISUSE OF GOVERNOR GROUND LAND REGARDING LAND FUNCTION TRANSFER - Afiyah, Siti; Masruroh, Ainul; Putri, Dita Karunia Malika; Sundari, Ariefah (SYNTIFIC, 2025)
Background. Governor Ground land refers to land without ownership rights, which can be interpreted as abandoned land. Abandoned land is land controlled by the state where the legal relationship between the landowner and the land has been severed, as regulated in Article 27(a) of the Basic Agrarian Law (UUPA). The government's authority over such land is specified in Article 2, paragraph (2) of the UUPA. This study aims to provide answers regarding the rights over Governor Ground land. Research Methods. The research employs normative legal methods, using a conceptual, case, and legislative approach. Legal materials were collected through literature review and analysis of articles and opinions from previous researchers. Findings. Governor Ground land can be owned or utilized if specific requirements are met and permission is obtained from the government, particularly the National Land Agency (BPN). Governor Ground is land that has no ownership rights and can be considered as abandoned land. The community can use it for the common interest in accordance with the procedures in the Law. Conclusion. This land can have rights such as HGU, HGB, and Right to Use. If these rights are misused, they can be subject to criminal penalties with a sentence of three months or a fine of up to IDR 10,000. If the land is not maintained, the government can take back the land and demolish the buildings on it.